Applications of ultra-high-field magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy (¹H-MRS) in preclinical research - Mali, Ivina (Kansas State University, 2022)
Magnetic resonance imaging (MRI) is widely used to non-invasively evaluate anatomical and physiological properties of tissues in both clinical and preclinical studies making it the gold standard in medical imaging. The protocols and workflows for MRI are well established; such is not the case for Magnetic Resonance Spectroscopy (MRS). In contrast to MRI or as a complement, MRS provides biochemical composition and quantitative information of the tissue being analyzed. Modern MRI scanners can be used for MRS without any hardware modifications. MR scanners used in the clinic are of low field strength (1.5 Tesla (T) or 3 T) and require contrast agents to improve the visibility of tissue structures. On the other hand, small animal imaging requires scanners of high field strength to acquire higher resolutions to visualize similar structures and produce clinically translatable results. In this study, we use an ultra-high-field scanner of 14.1 T and optimized pulse sequences to obtain MRI and image-guided-MRS data of high spatial and spectral resolution, respectively. This work focuses on small animal models of solid tumors and neurological disorders. We monitored the growth of pancreatic ductal adenocarcinomas (PDAC) on C57BL/6 mice using a RARE (Rapid Acquisition with Relaxation Enhancement) pulse sequence after tumor implantation. MRI-guided thermal treatments were applied to mouse models of PDACs and aldosterone-producing adenoma in vivo. To evaluate the tissues before and after treatment, T1 mapping techniques were used. Another objective of this study was to use single voxel ¹H-MRS (Proton MRS) techniques to study metabolite levels in cell lines and tissues ex vivo. We used a PRESS (Point RESolved Spectroscopy) sequence to acquire spectral information from five different cell lines (four cancer and one non-cancer) and solid tumors excised from mouse models and human subjects. Short, intermediate, and long echo times (TEs) were explored where short TE was found effective in resolving major metabolites compared to conventional long TE scans. Spectra with high SNR (signal-to-noise ratio) were acquired from voxel sizes up to 2 x 2 x 2 mm³. The current work also uses the valproic acid (VPA) model of autism spectrum disorder (ASD) in rodents. We collected 3D MRI scans to measure gray matter volumes in cerebellar and frontal regions of VPA-treated and control rat brains ex vivo. High-resolution MRI data allowed accurate segmentation across different regions of the rat brains. Altogether, we demonstrate diverse applications of MRI and image-guided ¹H-MRS in preclinical studies using an ultra-high-field scanner.
Keywords: MRI; MRS; T1 relaxation; Thermal therapy; VPA rats